2022
DOI: 10.3390/foods11020145
|View full text |Cite
|
Sign up to set email alerts
|

RP-HPLC-ESI-QTOF-MS Qualitative Profiling, Antioxidant, Anti-Enzymatic, Anti-Inflammatory, and Non-Cytotoxic Properties of Ephedra alata Monjauzeana

Abstract: An investigation was conducted to study the beneficial effects of Ephedra alata monjauzeana crude extract (EamCE). The chemical profile was determined using RP-HPLC–ESI-QTOF-MS analysis, revealing the presence of twenty-one flavonoids and phenolic acids. A series of antioxidant assays was carried out using ten different methods. The EamCE has demonstrated a significant antioxidant potential, with interesting IC50 values not exceeding 40 µg/mL in almost activities. Likewise, a significant inhibition of key enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Ephedra alata was an important source of various bio-actives drugs such glycosides, flavonoids, phenolic compounds, and alkaloids. Previous studies reported have reported that this plant exert identical biological activities as antibacterial, liver function protection, prevention of cardiovascular diseases, and prevention and amelioration of cancer [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. A number of natural products possess the ability to prevent obesity by digestive enzymes as lipase and α-amylase [ 6 , [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…Ephedra alata was an important source of various bio-actives drugs such glycosides, flavonoids, phenolic compounds, and alkaloids. Previous studies reported have reported that this plant exert identical biological activities as antibacterial, liver function protection, prevention of cardiovascular diseases, and prevention and amelioration of cancer [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. A number of natural products possess the ability to prevent obesity by digestive enzymes as lipase and α-amylase [ 6 , [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…The depletion of the acetylcholine (ACh) neurotransmitter by cholinesterase is linked to Alzheimer’s etiology [ 7 ]. Currently, the most successful therapeutic strategy is the application of ChE inhibitors [ 8 ], particularly natural anticholinesterases and antioxidants. As most of these medicines have numerous adverse effects, it is desirable to use and manage them effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another study carried out by Soumaya et al [ 5 ] confirmed the presence of gallic acid, catechin, caffeic acid, ferulic acid, rutin, and quercetin in the E. alata aerial part extract depending on the extraction solvent polarities. Additionally, Khattabi et al [ 10 ] characterized 21 compounds in the aerial parts of E. alata including caffeic acid, gallic acid, quercetin-O-rhamnoside, hyperoside, quercetin-3-O-galactoside, isorhamnetin-3-O-glucoside, quercetin-3-O-glucoside, and epicatechin based on RP-HPLC-ESI-QTOF-MS qualitative profiling. While the LC-DAD-ESI-MSn analysis proved that isoflavones and flavonol derivatives were the major compounds [ 48 ].…”
Section: Resultsmentioning
confidence: 99%